Socio-Cultural and Economic Impact of Corona Virus on Cancer Patients, Caregivers and Survivors - Wasimul Hoda; Sachidanand Jee Bharati; Abhinav Kumar; Priyanka Choudhary; Abhishek Shankar (Asian Pacific Journal of Cancer Care, 2020)
Corona Virus Disease -19 (COVID-19) pandemic has a widespread impact on social, cultural and economic aspects of life. It has affected cancer patients in a big way because with onset of COVID-19 pandemic, the healthcare resources were diverted to handle Corona virus infection. The cancer patient, their caregivers and healthcare professional are in dilemma of whether to continue the treatment or stop it for some time till COVID-19 infection settled down. The long-lasting effect of COVID-19 pandemic on socio-economic and mental health of cancer patients and health care workers will emerge in times to come. It is important that a tight balance be made between cancer treatment and its interruption due to COVID-19.